Carboxymethyl Cellulose Photocracking by Magnetic Recoverable Photocatalyst to Produce Biofuel in Ambient Condition - Ramanda, Yudha; Thomas, Kevin; Aziz, Saifuddin; Mauludi, Kurniawan; Kunarti, Eko Sri (Chimica et Natura Acta, 2017)
Synthesis of Fe3O4/SiO2/TiO2 nanocomposite and its application as photocatalyst in Carboxymethyl Cellulose (CMC) photocracking had been conducted. Magnetite preparation was carried out by sono-coprecipitation method. The deposition of SiO2 and TiO2 were performed by sol-gel method under ultrasonic irradiation. All material products were characterized by X-ray diffraction (XRD), Fourier transform infra-red spectrophotometry (FT-IR), and transmission electron microscopy (TEM). The final material product was also analysed by specular reflectance UV-Visible (SR-UV-Vis). The product of photocracking was analysed by gas chromatography â mass spectrometry (GC-MS).The XRD diffractogram and FT-IR spectra confirmed the presence of Fe3O4, SiO2, and anatase phase of TiO2. The TEM image revealed the presence of nanocomposite with core-shell structure. The SR-UV-Vis spectrum was used to determine band gap energy of the photocatalyst and it gave a result of 3.22 eV. The GC chromatogram of photocracking product indicated some major fractions. The MS spectra showed that some major fractions were smaller molecules including methanol, the component of biofuel.